A solid organising cryptogenic liver abscess and its association with a colonic tubullovillous adenoma. (9th July 2012) - Tan, Christopher B; Shah, Mitanshu; Rajan, Dhyan; Lipka, Seth; Ahmed, Shadab; Freedman, Lester; Rizvon, Kaleem; Mustacchia, Paul
Abstract : Cryptogenic liver abscess (CLA) is a well-known disease entity that has puzzled clinicians for centuries. With the advancement of diagnostic modalities, comes the decreasing incidence of liver abscess labelled as 'cryptogenic' in nature. Colonic diseases have been identified as a possible underlying condition found in patients with liver abscesses. Although rare, tubullovillous adenomas have been implicated as one of the colonic causes of a CLA. We present a case of a CLA in a 53-year-old man with a potentially associated tubullovillous adenoma found via colonoscopy.